Scripting your voice as a method for achieving originality. Issue 3 (2nd July 2020) - Dean, Levi
ABSTRACT: This article explores how screenwriters can discover and inject their voice into their screenplay, as a method for achieving originality. It should be noted that the study is exclusively concerned with screenwriters scripting for the commercial market. The definition formed on originality reflects this industrial position. Originality, therefore, is defined as a screenwriter successfully synthesising storytelling principles with their own voice to render something new. However, what precisely comprises voice is nebulous. To resolve this, the article will first need to critically explore writer's voice to frame a precise definition. Once this has been accomplished, a new conceptual framework, Cracks of Culture, is presented as a formula to guide screenwriters to discover and inject their own voice. The concept is underpinned by leading philosopher and neuroscientist, Antonio Damasio's [2018. The Strange Order of Things: Life, Feeling, and the Making of Cultures . New York: Vintage Books] notion that, culture expresses all categories, which gives rise to the social order and structure of a society. Finally, the article demonstrates how screenwriters can authentically voice a character of an opposite gender. This method is then presented as a possible tool for writers wishing to voice other social groups, inciting the author to call upon further research to explore this hypothesis further.